2000
DOI: 10.1038/sj.gt.3301209
|View full text |Cite
|
Sign up to set email alerts
|

B7.1 expression by the weakly immunogenic F98 rat glioma does not enhance immunogenicity

Abstract: Enhanced immunogenicity has been reported following transfection of a variety of immunogenic tumors with the B7.1 co-stimulatory molecule. The purpose of the present study was to determine if transfection of a weakly immunogenic rat brain tumor, the F98 glioma, with the gene encoding B7.1 could enhance its immunogenicity. F98 cells were transfected with a plasmid containing the B7.1 gene, and stable transfectants (F98/B7.1) were obtained. Flow cytometric analysis confirmed the expression of B7.1 and MHC class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Many tumors, however, display defects in antigen processing and presentation 42 and are poorly immunogenic even after transduction with cytokines or costimulatory molecules. 13,14 To overcome these limitations, we constructed chimeric antibody receptors to activate T cells at the local tumor environment directly. We found that expression of membrane-bound anti-CD3 receptors with CD80 or CD86 induced the proliferation of both CD4 + and CD8 + T cells, reduced the threshold for T-cell activation, stimulated prolific IL-2 production and generated T-cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many tumors, however, display defects in antigen processing and presentation 42 and are poorly immunogenic even after transduction with cytokines or costimulatory molecules. 13,14 To overcome these limitations, we constructed chimeric antibody receptors to activate T cells at the local tumor environment directly. We found that expression of membrane-bound anti-CD3 receptors with CD80 or CD86 induced the proliferation of both CD4 + and CD8 + T cells, reduced the threshold for T-cell activation, stimulated prolific IL-2 production and generated T-cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Tumors that express low amounts of MHC class I molecules or process antigens poorly cannot effectively trigger T cells and transduction with CD80 or CD86 fails to induce tumor rejection. 13,14 An alternative strategy to activate T cells that is less dependent on the expression of tumor-associated antigens or MHC molecules by tumor cells may extend the utility of immunotherapy to poorly immunogenic tumors. We and others have previously shown that cells modified to express chimeric anti-CD3 receptors can activate naive T cells.…”
mentioning
confidence: 99%
“…© 2005 American Association for Cancer clincancerres.aacrjournals.org Downloaded from death, and trigger natural killer cell cytotoxicity (19,20). Whereas conferring B7 expression on tumor cells can enhance antitumor responses, it is also apparent that provision of B7 expression is not sufficient to induce immunity against nonimmunogenic tumors (21). Combining B7 expression with immune-stimulatory cytokine expression has been shown to augment tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The F98 glioma is poorly immunogenic (30), and ways to enhance its immunogenicity have been sought without success (31). Rats that were rendered disease free were immune to intracerebral rechallenge.…”
Section: Discussionmentioning
confidence: 99%